1450. Trends in hospitalizations and outpatient visits with early or delayed antibiotic treatment initiation in nontuberculous mycobacterial lung disease. (15th December 2022) - Winthrop, Kevin L; Waweru, Catherine; Hassan, Mariam; Pharm, B; Burns, Sara; Chatterjee, Anjan
Abstract: Background: The 2020 treatment guidelines for patients diagnosed with nontuberculous mycobacterial lung disease (NTMLD) recommend antibiotic treatment initiation rather than "watchful waiting" for most patients. Little is known regarding how delayed treatment (DT) may impact healthcare resource utilization (HRU). The goal of this study was to assess HRU with early antibiotic treatment (ET) or DT in NTMLD. Methods: We conducted a retrospective observational cohort study using MarketScan claims from July 2014 to June 2020. Inclusion criteria were: ≥ 2 NTMLD medical claims (with date of first NTMLD claim as index date); continuous enrollment spanning 12 months pre–index date (baseline) to ≥ 24 months post–index date; concomitant treatment with antibiotics used in NTMLD, ie, from ≥ 2 drug classes within 28 days of each other; and no tuberculosis diagnosis. Mean time to antibiotic initiation (TT) from index date was used to define ET (TT ≤ 3 months) and DT (TT > 3 months) groups. Trends in hospitalizations (any, respiratory-related) and any outpatient visits at baseline, year 1 (Y1), and year 2 (Y2) post–index date were described. Results: A total of 518 patients with NTMLD were included: 395 (76%) ET and 123 (24%) DT patients. ET patients tended to be younger and male; DT patients had a higher prevalence of emphysema, asthma, and bronchiectasis. ET patients had a decrease from baseline in the proportion of patients hospitalized and the mean number of hospitalizations at Y1 and Y2 (Figure 1A and 1B ). DT patients had an increase from baseline in the proportion of patients hospitalized and the mean number of hospitalizations at Y1, followed by a decrease in Y2, although the mean number of hospitalizations at Y2 remained higher than at baseline. Similar trends in respiratory-related hospitalizations were observed per patient group (Figure 1C and 1D ). ET patients had a decrease from baseline in the proportion of patients and the mean number of emergency room visits at Y1 and Y2, whereas DT patients showed little to no improvement (Figure 2A and 2B ). Figure 1. Proportion of patients with (A) any hospitalization and (C) respiratory disease–related hospitalizations with early or delayed treatment for NTMLD. Mean number of (B) any hospitalizations and (D) respiratory disease–related hospitalizations per patient with early or delayed treatment for NTMLD Figure 2. (A) Proportion of patients with any ER visits with early or delayed treatment for NTMLD. (B) Number of ER visits per patient with early or delayed treatment for NTMLD Conclusion: During the first 2 years after diagnosis, improvements in hospitalizations and ER visits were observed in patients who received ET, whereas patients who received DT showed little to no improvement from baseline. Disclosures: Kevin L. Winthrop, MD, MPH, AN2: Advisor/Consultant|AN2: Grant/Research Support|Insmed: Advisor/Consultant|Insmed: Grant/Research Support|Paratek: Advisor/Consultant|Paratek: Grant/Research Support|Red Hill Biopharma: Advisor/Consultant|Red Hill Biopharma: Grant/Research Support|Spero Therapeutics: Advisor/Consultant Catherine Waweru, PhD, Insmed Incorporated: Employee|Insmed Incorporated: Stocks/Bonds Mariam Hassan, PhD, B. Pharm, Insmed Incorporated: Employee|Insmed Incorporated: Stocks/Bonds Sara Burns, MS, Panalgo: Employee Anjan Chatterjee, MD, MPH, Insmed Incorporated: Employee|Insmed Incorporated: Stocks/Bonds.